Cinnamon Essential Oil Nanocellulose-Based Pickering Emulsions: Processing Parameters Effect on Their Formation, Stabilization, and Antimicrobial Activity - Alana Gabrieli de Souza; Rafaela Reis Ferreira; Elisa Silva Freire Aguilar; Leonardo Zanata; Derval dos Santos Rosa (Polysaccharides, 2021)
This work aimed to prepare nanocellulose-based Pickering emulsions using cinnamon essential oil. Different formulations were investigated by varying the preparation time, homogenization speed, oil and nanocellulose concentration, and morphology. The emulsions were first characterized by droplet size, morphologies, and storage stability. The Design of Experiments (DoE) was used to evaluate the parameter’s effects on the emulsions’ stability, and the emulsions with optimum particle size and stability were evaluated by antimicrobial activity. The more stable emulsions required higher energy in the system to obtain efficient emulsification. The cellulose nanocrystal (CNC) emulsions showed a 30% oil volume as a constant to obtain a low creaming index (34.4% and 42.8%) and zeta potential values around −29 mV, indicating an electrostatic stabilization. The cellulose nanofiber (CNF) emulsions showed 100% stability after a month using a 20% oil volume as a constant and Zeta potential values around −15 mV, indicating a steric stabilization. CNF-emulsions’ inhibition halos for Bacilus subtilis were 30.1 ± 3.7% smaller than those found in CNC-emulsions (65 ± 2.9 mm), while Pseudomonasaeruginosas almost do not present differences in the inhibition halos. These results suggest that the nanocellulose morphology may promote a regulation on the EO migration to the medium, as well that this migration ratio does not affect the bacteria.